Implications of standards in setting environmental policy. Issue 98 (August 2019) - Goulden, Shula; Negev, Maya; Reicher, Shay; Berman, Tamar
Highlights: Both voluntary and mandatory standards raise issues for environmental policy. Standard-setting is affected by resources, pragmatism and economic considerations. Despite limitations, standards may take the place of government-set regulation. Standards for environmental policy should take account of sources of bias. Improving representation and government's role could improve standard-setting. Abstract: As a tool to regulate environmental issues, standards play a key role in defining acceptable levels of safety and environmental protection. From a governance perspective, standards are also significant for their inclusion of non-governmental stakeholders, including industry and environmental organizations, in determining the benchmarks upon which policies are enacted. Drawing upon work on Israeli standards for both environmental pollutants in consumer products and 'green building', this paper considers how the use of standards as an environmental policy tool affects how environmental issues are regulated. The research uses written standards, research into standardisation committees and approximately twenty in-depth interviews. Thematic analysis of the use of these standards as environmental policy tools highlighted different issues including the connection between representation of different interests and availability of resources; different rationales for standards that may produce conflict in professional decisions; and implications of the consensus-building approach for balancing interests and driving government policy. We conclude that various factors ought to be taken into account when using standards within environmental policy. We provide policy recommendations including a need to consider the implications of using a standard in the absence of broader regulation; the impact of economic and pragmatic rationales on environmental and health measures in standards; and means to improve the balance of representatives on standards committees.